Instrumentation reference book - Boyes, Walt. (Boston : Butterworth-Heinemann, 2003)
Instrumentation is not a clearly defined subject, having a 'fuzzy' boundary with a number of other disciplines. Often categorized as either 'techniques' or 'applications' this book addresses the various applications that may be needed with reference to the practical techniques that are available for the instrumentation or measurement of a specific physical quantity or quality. This makes it of direct interest to anyone working in the process, control and instrumentation fields where these measurements are essential. The latest edition of the Instrumentation Reference Book is a comprehensive and authoritative collection of technical information, which is of direct practical value to instrumentation and control engineers as well as all instrument technicians and users. It is also an indispensable addition to any academic library for the benefit of engineering and science students. Written by a collection of specialist contributors under the guidance of Walt Boyes, the third edition of this book (developed from the work originally published for more than 40 years as Jones Instrument Technology) has been updated to include chapters on the fieldbus standards, reliability, EMC, 'virtual instrumentation', fibre optics, smart and intelligent transmitters, analyzers, level and flow meters, and many more. * Comprehensive and authoritative collection of technical information * Written by a collection of specialist contributors * Updated to include chapters on the fieldbus standards, reliability, EMC, 'virtual instrumentation', fibre optics, smart and intelligent transmitters, analyzers, level and flow meters, and many more.
Mechanical measurements -- Measurement of temperature and chemical composition -- Electrical and radiation measurements -- Instrumentation systems -- Further scientific and technical information.
Includes bibliographical references and index.
Keywords: Physical instruments -- Handbooks, manuals, etc; Engineering instruments -- Handbooks, manuals, etc; Electronic books; Handbooks, manuals, etc